2001
DOI: 10.1002/1097-4636(20010605)55:3<313::aid-jbm1019>3.0.co;2-e
|View full text |Cite
|
Sign up to set email alerts
|

Preferential degradation of osteoclasts by titanium tetrachloride

Abstract: Although titanium alloys are known to be biocompatible with bone tissue after implantation in human beings, the effect of titanium on osteoclasts remains to be studied. We examined the effect of titanium salt on the formation and survival of osteoclasts in cell culture. The addition of 10 microM titanium tetrachloride caused a decrease in the cell number of osteoclast-like cells induced in bone marrow cell cultures taken from mice. The addition of 10 microM titanium tetrachloride caused degradation of the disa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…However, recent evidence shows that these inflammatory responses to Ti particles are based on the adherent endotoxin to Ti particles (Bi et al , 2001) and that Ti ions inhibit osteoclast formation induced by PGE 2 . In an in vitro study Matsunaga et al (2001) questioned whether Ti particles are directly involved in osteolysis caused by wear debris. In the present study, we found, rather unexpectedly, that Ti particles with no adherent endotoxin inhibited osteoclastogenesis without affecting osteoclastic bone resorbing activity.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent evidence shows that these inflammatory responses to Ti particles are based on the adherent endotoxin to Ti particles (Bi et al , 2001) and that Ti ions inhibit osteoclast formation induced by PGE 2 . In an in vitro study Matsunaga et al (2001) questioned whether Ti particles are directly involved in osteolysis caused by wear debris. In the present study, we found, rather unexpectedly, that Ti particles with no adherent endotoxin inhibited osteoclastogenesis without affecting osteoclastic bone resorbing activity.…”
Section: Discussionmentioning
confidence: 99%
“…Some data indicates they promote osteoclast-induced bone resorption, possibly through cytokine modulation. Other data indicates titanium ions induce osteoclast apoptosis [13,88,290].…”
Section: Titaniummentioning
confidence: 99%
“…Apoptosis, or physiologic cell death, is based on an endogenous cell suicide mechanism, which can be selectively triggered by the cells in response to as-yet-largely-unknown stimuli (Cohen, 1993). Recently, it has been shown that titanium ions cause a preferential degradation of osteoclasts rather than osteoblasts, most likely by an apoptotic mechanism (Matsunaga et al, 2001). However, studies regarding the effects on apoptosis of surface topography of titanium dental implants are limited, and such effects, if any, are largely unknown.…”
Section: Introductionmentioning
confidence: 99%